Market structure, common ownership and coordinated manager compensation - Werner Neus; Manfred Stadler; Maximiliane Unsorg (University of Tübingen, Faculty of Economics and Social Sciences, 2020)
We study oligopolistic competition in product markets where the firms' quantity decisions are delegated to managers. Some firms are commonly owned by shareholders such as index funds whereas the other firms are owned by independent shareholders. Under such an asymmetric ownership structure, the common owners have an incentive to coordinate when designing the manager compensation schemes. This implicit collusion induces a less aggressive output behavior by the coordinated firms and a more aggressive behavior by the noncoordinated firms. The profits of the noncoordinated firms are increasing in the number of coordinated firms. The profits of the coordinated firms exceed the profits without coordination if at least 80 % of the firms are commonly owned - an astonishing resemblance to the merger literature.
urn:nbn:de:bsz:21-dspace-991497
Keywords: G32; L22; M52; 330; Common ownership; index funds; shareholder coordination; manager com-pensation